DISTINCTIVE QUALITIES OF BACHELOR OF TECHNICAL-VOCATIONAL PROGRAM AS A CAREER CHOICE: BASIS FOR SPECIALIZED SUBJECT OF GRADE 12 STUDENTS (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
Senior high school graduates face one of the most significant decisions of their lives: selecting a program that will influence their future. This decision often brings about stress and confusion, as students struggle to choose a program that aligns with their aspirations. Rather than thoroughly researching and comparing available programs, many students who have completed the Technical Vocational Livelihood (TVL) track end up pursuing a different program altogether. This raises important questions about the factors influencing TVL students' decisions to enroll in the Bachelor of Technical-Vocational Teacher Education (BTVTED) program and how these factors shape their future career choices. Understanding these influencing factors is crucial for guiding students in making informed decisions that will lead to successful and fulfilling careers. The researchers used a simple random sampling technique to select the respondents. Printed questionnaires and checklists were distributed for data collection. The gathered data were analyzed and processed statistically. To identify the key factors influencing the choice of the Bachelor of Technical-Vocational Education and Training (BTVTED) program, the researchers employed weighted mean analysis. The study highlights that students encounter challenges in selecting BTVTED as their college career path. Peer pressure is one of the key factors influencing their decision, with 13 respondents indicating its impact. Family-related issues also play a role, with 15 respondents mentioning it as a concern. However, the most significant barrier identified by the majority of respondents is financial difficulty, which hinders their ability to pursue the program. The main objective of this study is to examine the factors influencing technical-vocational students' choices of academic programs that align with their career goals. The study highlights the importance of providing comprehensive career guidance and market-awareness programs in vocational education, enabling students to make informed decisions about their future careers. The findings suggest that students' program choices are primarily influenced by their personal interests, career aspirations, and the desire for expert advice. Moreover, addressing financial barriers, which are the most significant obstacle, can be achieved by promoting the BTVTED program through social media and offering resources such as scholarship information and requirements to help students navigate these challenges.
Keywords: factors influencing career choices; technical-vocational education and training (tvet); btvted program; career guidance; market-awareness programs; student decision-making; vocational education; scholarship opportunities; financial barriers